Trema micrantha Blume na alimentação de poedeiras comerciais (*) - Ariki, Joji [UNESP]; Donola, Edmur; Macedo, Elisabete Maria; Rodrigues, Maria Emília; Rodrigues, Angela Maria (Instituto Nacional de Pesquisas da Amazônia, 1980)
A trial was carried out to observe the effect of inclusion of Trema micrantha dried at levels of 0.0, 2.0, 4.0, 6.0, and 8.0% in hens diets. Although no statistical diference were observed between the treatments, the diet with 4% of dried trema did not change hens performance. Data of egg yolkcolor demonstrated that trema dried meal were a source of xanthophyll, increasing the egg yolkcolor, according as the following equation. Y = 8,5 + 0,4 x where, y = egg Yolkcolor and X = % of trema in the diet.